Effect of Rainfall Intensity and Initial Matric Suction on the Stability of Residuals Soils Slope - Agus Setyo Muntohar, Muhammad Suradi, Andy Fourie (2014)
Seepage and slope stability issues concerning infiltration in unsaturated slopes are investigated and presented. A two dimensional transient finite element analyses are used to study the effects of the rainfall intensity and initial matric suction on the stability of slope in tropical region in Northern Territory, Australia. The Jabiru landslide occurred in March 2007 after severe rainstorm with rainfall amount of 0.8 m in 3 days. This landslide occurred at a soil slope with height . Field and laboratory investigations were carried out to determine soil parameters required in slope stability analysis. Parametric study was performed to find out which cases with respect to rainfall intensity and initial matric suction triggering the landslide occurrence. The results indicates that if the rainfall intensity is greater or equal to the saturated hydraulic conductivity of the soil , the slope stability is controlled by the saturated hydraulic conductivity of the soil. In general, the results conclude that the slope stability is highly dependent on the initial matric suction.